2009
DOI: 10.1007/s00359-009-0431-x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and optics of the eyes of the box jellyfish Chiropsella bronzie

Abstract: Cubomedusae have a total of 24 eyes of four morphologically different types. Two of these eye types are camera-type eyes (upper and lower lens-eye), while the other two eye types are simpler pigment pit eyes (pit and slit eye). Here, we give a description of the visual system of the box jellyfish species Chiropsella bronzie and the optics of the lens eyes in this species. One aim of this study is to distinguish between general cubozoan features and species-specific features in the layout and optics of the eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…Light microscopy and ultrastructural studies confirm the position of the nuclei in the cell bodies (Figure 6) [32], [34]. Our leo expression results are consistent with Koyanagi et al [17], but different from the results of Kozmik et al [18] who reported a different gene ( Tc-neo ) to be expressed in lens eyes with a maximal sensitivity to blue light (470 nm) in in vitro expression analysis.…”
Section: Discussionsupporting
confidence: 81%
“…Light microscopy and ultrastructural studies confirm the position of the nuclei in the cell bodies (Figure 6) [32], [34]. Our leo expression results are consistent with Koyanagi et al [17], but different from the results of Kozmik et al [18] who reported a different gene ( Tc-neo ) to be expressed in lens eyes with a maximal sensitivity to blue light (470 nm) in in vitro expression analysis.…”
Section: Discussionsupporting
confidence: 81%
“…Hence, rates of visual pigment regeneration may differ between the two lens eyes. One morphological difference between the lens eyes is the presence of long-pigmented cells in the lower lens eye (O'Connor et al 2009, figure 5a). It is possible that the long-pigmented cells take part in photopigment regeneration, resulting in a proportionally larger amount of regeneration components available in the lower lens eye than in the upper lens eye.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the four rhopalia contains two lensed, complex eyes, two pit ocelli, two slit ocelli, a statolith-like concretion, sensory epithelia, a 'central' neuropil of neuronal processes and synapses, and an outer layer of neuronal and non-neuronal somata (Berger, 1898;Laska and Hundgen, 1982;Nilsson et al, 2005;O'Connor et al, 2009). In all anatomical respects, these latter structures give the rhopalia the look of ganglia found in bilateral animals (Fig.10).…”
Section: Peripheral Integration and The Scyphozoan Swim Systemmentioning
confidence: 96%